PREVALENCE OF FEMALE LOWER URINARY TRACT SYMPTOMS (FLUTS) IN PAKISTAN. A POPULATION BASED MULTI-CENTER STUDY - Shamsher, Saadia; Gul, Bakhtawar; Sheikh, Masood Ahmed; Yasmeen, Haleema; Zahoor, Saadia; Ali, Shahzad; Niaz, Waqar Azim (Khyber Journal of Medical Sciences, 2025)
Background: FLUTS affected about 2.3 billion (45.8%) people of the world population in 2018. It is more common among females and mostly affects multiparous and elderly females. Objectives: This study aimed to find out the prevalence of lower urinary tract symptoms and its association with quality of life within a population-representative sample of women aged between 18 to 70 years in Pakistan Methods: This was a multicenter prevalence study based on a cross-sectional survey of seven centers of Pakistan among women aged between 18-70 years. Prevalence of FLUTS and its relation with demographic factors like age, parity, mode of delivery, and socioeconomic conditions data was collected. Results: In this study, the prevalence of LUTS ranges from 4.31- 44.31%. Nocturia was the highest complaint with (44.31%) followed by urgency (35.60 %), suprapubic pain in association with mostly spontaneous vaginal delivery (45.6%). Voiding symptoms are more common than storage. The most bothersome symptoms were nocturnal enuresis (56.03 %). The most common age group is 18-30 years with 44.9 %. Mostly females were of a low socioeconomic status. FLUTS is more common in nulliparous women (55.6%). Conclusion: FLUTS is a significant problem among women in Pakistan and has a significant impact on quality of life, mental health, and work productivity. Overall, the correlation between LUTS in female’s age, parity, mode of delivery, and socioeconomic status highlights the early detection and management. It is necessary to educate females regarding FLUTS, due to its high prevalence.